Model Penentuan Hari Dari Sebuah Tanggal - Randy Rahayu Melta; Media Rosha; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2018)
Abstract –This article discusses the pricing models of a date. This discussion began by making Sunday of date January 1, 1758M as a reference for determine desired day. This is due before 1758M the time was corrected that cause in a year have an irregular pattern. An models analysis using modulo 7, that can implemented to Turbo Pascal algorithm by entering the date, month and year which are desired so that obtained the desired day.